If it's not what You are looking for type in the equation solver your own equation and let us solve it.
60+x=0.9*(6+x)
We simplify the equation to the form, which is simple to understand
60+x=0.9*(6+x)
Reorder the terms in parentheses
60+x=+(+5.4 + 0.9x)
Remove unnecessary parentheses
+60+x=+5.4 + 0.9x
We move all terms containing x to the left and all other terms to the right.
+1x-0.9x=+5.4-60
We simplify left and right side of the equation.
+ 0.1x=-54.6
We divide both sides of the equation by 0.1 to get x.
x=-546
| 15x^2+19x+5=7x+8x^2 | | (0)=4x+6 | | 49x^2-25y^2+0=0 | | y=-2x+11 | | 49x^2-25y^2=0 | | y=4(-4)+6 | | 100-2*x=10+x | | (x+5)(x-5)=9 | | 5y-2x=0 | | 6/4064=x | | 9p-p=4p-11 | | 6/4064= | | 110-2*x=12+x | | -3x-8=2x+2 | | 9(4x+7)-4=8(7x+3)-3x | | 128x=48+4x | | x-3(0)=-6 | | 5m-5=n+10 | | 11-8x=65-22x | | 4(4x-3)=2(9x+5)-8 | | -3/4+1/2=r | | 18-6(x-2)=45 | | 9+2x=27 | | -3-5x=2x-11 | | -3-5=2x-11 | | 28-4n= | | 5x^2+10x-6=0 | | 6x-6*6=5 | | 8x^2+7x-7=0 | | .00000000023= | | 8x=128x | | 75-3x=33x+15 |